EXPRESSION OF EMOTIONAL INTELLIGENCE IN ACTIVITIES OF COMMUNITY SOCIAL WORKER - Leliūgienė, Irena; Kaušylienė, Angelė; Veikšrienė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Referring to scientific literature, the article aims to define definition and model Emotional intelligence (EI). Emotional intelligence (EI), the term first used in 1966, is still considered a new area of science.  The increase in requirements for social workers and their personal and professional qualities made it important to know their own emotions and those of the others and manage them. Personal qualities – self-awareness, motivation, flexibility, interpersonal skills, the ability to adapt to change, to understand and recognize emotions is very important to the social worker's activities. Management of emotional intelligence in the personal and interpersonal community social worker activities is one of the main acts in relations with others. Expression of emotional intelligence in activities of community social worker is the object of this paper. The theoretical part of the work substantiates the theory of emotional intelligence expression in activities of community social worker after discussing emotional intelligence. The research empirically investigated social workers opinions about the expression of emotional intelligence community. The study uses the following methods: analysis of documents, scientific and methodological literature, websites, quantitative research method, questionnaire survey. The study was carried out in questionnaire method, interviewing 212 respondents in 44 institutions. Results of the study confirmed the hypothesis that community social worker activities is worth to foster through self-improvement of emotional intelligence expression.